1981
DOI: 10.2307/3225800
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Characterization of Aquatic Environments Using Diatom Life-Form Strategies

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…A. minutissima is a common and frequently dominant member of the periphyton in a wide variety of situations (Allanson 1973, Brown and Austin 1973, Kuhn et al 1981, and was inferred by Williams et al (1973) sponses is shown in Fig. 4, modified from Smith's (1982) description of N:P requirements of phytoplankton.…”
Section: Algal Response To N Additionmentioning
confidence: 98%
See 1 more Smart Citation
“…A. minutissima is a common and frequently dominant member of the periphyton in a wide variety of situations (Allanson 1973, Brown and Austin 1973, Kuhn et al 1981, and was inferred by Williams et al (1973) sponses is shown in Fig. 4, modified from Smith's (1982) description of N:P requirements of phytoplankton.…”
Section: Algal Response To N Additionmentioning
confidence: 98%
“…ton, algal periphyton growth may also be used to assess the form of nutrient limitation, as shown by Wuhrmann and Eichenberger (1974), Stockner and Shortreed (1978), Marcus (1980), Krewer and Holm (1982) and Peterson et al (1983) for streams, and Sladeckova (1979) for lakes. Periphyton, because they are attached, are especially useful as biological indicators of point sources of nutrients in lakes (Kuhn et al 1981). Localized supplies of particular ions from natural springs, influent streams, or sewage outfalls, for example, may have little impact upon the water chemistry or phytoplankton of a lake, but may cause identifiable changes in periphyton attached to nearby substrates (Stevenson and Stoermer 1982).…”
Section: Introductionmentioning
confidence: 99%
“…The community succession rate was measured by average dissimilarity between successive sampling days ( Kuhn et al 1981). The Shannon-Wiener index of diversity was calculated using a logarithm in base 2 transformation (Shannon and Weaver 1963).…”
Section: Methodsmentioning
confidence: 99%
“…For analysis of the diatom growth-forms, including slowly moving, moving, and stalked diatoms, particular species in the examined material were selected according Kuhn et al (1981).…”
Section: Methodsmentioning
confidence: 99%